Ageing and sex attraction of Teratorhabditis nematode (Acta Scientiarum. Animal Sciences, 2026)
Sex attraction was observed in the free - living nematode Teratorhabdits palmarum (Gerber & Giblin-Davis, 1990). Attraction by means of pheromones provides the ability to find and distinguish appropriate individual with which to mate. In the present study, we performed sex attraction assay to examine whether males of different age groups or reproductive states respond to volatile sex attractants of females. In T. palmarum, young virgin males were strongly attracted to young virgin females but declined with their age. Young non - virgin males responded to young virgin females while they did not respond to ten - day old virgin female. Similarly, old but not young virgin males failed to respond to non - virgin females. Attraction of virgin and non - virgin males declined with their age and also declined or did not occur with increasing age of females. We also investigated the pheromone system of the gonochoristic nematode Teratorhabdits palmarum that produces sex - specific attractants of the opposite sex. Mass Spectrometric Analysis of the T. palmarum exometabolome revealed that females but not males, produce the male attracting ascr#1 and ascr#9, ascaroside previously identified from C. elegans and other nematodes. The specific function of these ascarosides would not be analysed, because these pheromones play different roles in different nematode species.